THE RELATIONSHIPS BETWEEN STUDENTS’ USE OF STRATEGIES AND THEIR PERFORMANCE ON SPEAKING TASK IN PPNS (NOBEL: Journal of Literature and Language Teaching, 2013)
This research was intended to meet the objective of the study: to examine the relationships between students’ use of strategies and their performance on speaking task. The research used a correlational quantitative design. There were two groups of students. Each group consists of 29 students. Both of the groups were chosen randomly. There were two types of research instruments that were used to collect the data from the experimental and control group; 1) speaking test, and 2) questionnaires. Those data then were analyzed to answer the research questions.This study used the statistical analysis (SPSS program) to analyze the data from pre-post speaking tests, the data from students’ learning strategies and their communicative competence, and the data from pre-post learning strategies questionnaires (SILL). The result of the statistical analysis shows that the hypotheses related to the research problems are accepted.This study revealed several important findings. Firstly, the student’s uses of language learning strategies are proven correlated with their communicative competence. The more the students use the language learning strategies, the higher the students’ communicative competence.Based on the result of this study, there were some suggestions made by the writer which are addressed to English teacher, students and future researchers. It is hoped that English teachers could not only how to teach the language, but also how to develop students’ learning strategies. Thus, learners are demanded to learn and use more learning strategies. The students may try or use any learning strategies which enable them to be better in speaking English. For the researchers, it is suggested to take the findings as well as the limitation of the present study for different level of students.Key Words: SILL, Strategies, Communicative Competence